Parametric approach to the reconstruction of timber structures in Campanian Roman houses - Luca Sbrogiò (Virtual Archaeology Review, 2022)
The virtual reconstruction of ancient architecture aims at describing the ‘original’ elevation and volume of a disappeared building. The feeble archaeological traces, often limited to their foundations, left by houses impair the reinstating of their image, in contrast to that which is made possible by the massive structures of public buildings. A twofold problem arises when dealing with timber structures during a reconstruction procedure: at the local scale of the individual beam (e.g. joists or rafters), one must define a beam’s cross-section given its span; at the overall scale, the shape of a building results from that which its structures allowed it to have been. Therefore, this work proposes a procedure to deal with the ‘local’ problem, i.e. the definition of a beam’s cross-section from its span. To that end, a simplified, parametric structural model is required. The available bits of information are organized into inputs, parameters and outputs of the analytical problem by matching each information with a structural quantity (load, cross-section, spacing, etc.). Two mathematical relationships among them are proposed, which express two equally possible dimensioning criteria, based either on joists’ strength or deformability. It seems that the joist’s strength was the option for lightly loaded joists, as in roofs or tightly spaced floor frames; conversely, heavily loaded joists conformed to the deformability criterion. Both dimensioning procedures are translated into a visual algorithm in Grasshopper, a plugin for Rhinoceros modelling software, which enables the parametric definition of objects. Finally, the proposed procedure is tentatively applied to automatically reconstruct the floor and roof frames that belonged to the domus on top of the Sarno Baths in Pompeii. The algorithm automatically picked the dimensioning criterion in relation to each frame’s span and hypothesized loads and determined joists’ orientation and minimum cross-sections. The obtained floor frames, whose structural conditions are considered as sensible, will be adopted in the overall virtual reconstruction proposal of the ruins, also based on the analytical evaluation of masonry structures.